Frequency of provision of knowledge of performance on skill acquisition in older persons - Nunes, Marcelo E. S.; Souza, Marina G. T. X.; Basso, Luciano; Monteiro, Carlos B. M.; Corrêa, Umberto C.; Santos, Suely (Frontiers in Psychology, 2014)
The provision of feedback is a crucial factor for the evolution of the learner’s performance. It is known that the knowledge of performance has the function of guiding the learner's attention to critical aspects of the movement pattern. The objective of this study was to examine the effect of frequency of knowledge of performance during the acquisition of the basketball free throw in older persons. Sixty active individuals (men and women) aged 60-69 years of age, divided into three experimental groups received knowledge of performance in 100%, 66% and 33% of their attempts during three practice sessions totaling 90 trials. The task was the basketball free throw. Volunteers were asked to conduct tests of immediate retention, 24h retention, and 24h transfer test, after the last practice session. During the acquisition phase, the volunteers received knowledge of performance on the movement pattern on the previous attempt, which was obtained from a qualitative hierarchical checklist of the free throw (14 items). Sessions were recorded in order to confirm whether volunteers were able to score throughout sessions. ANOVA indicated that all individuals showed an improved performance in the retention and transfer tests. But the knowledge of performance frequency of 66% was superior in both qualitative (movement pattern) and quantitative (score) measurements throughout the trials (p ≤ 0.05). In conclusion older persons seem to need an optimal Knowledge of Performance frequency supply during the learning process.